Exposure to nitroaromatic explosives and health effects during disposal of military waste. Issue 7 (1st July 2003) - Letzel, S; Göen, Th; Bader, M; Angerer, J; Kraus, T
Abstract : Aims: To investigate the exposure to dinitrotoluene (DNT) and trinitrotoluene (TNT) and the resulting effects in workers which occur during the disposal of military waste. Methods: Eighty two employees from a mechanical plant in Germany were studied, of whom 51 were regularly exposed to ammunition containing TNT and DNT, 19 occasionally, and 12 not at all. Results: Air analyses yielded maximum concentrations of 20 μg/m 3 for 2, 4-DNT and 3250 μg/m 3 for 2, 4, 6-TNT, respectively. The maximum concentrations in the urine of workers regularly exposed amounted to 5.0 μg/l of 2, 4, 6-TNT, 1464.0 μg/l of 2-amino-4, 6-dinitrotoluene, 6693.0 of μg/l 4-amino-2, 6-dinitrotoluene, 2.1 μg/l of 2, 4-DNT, 95.0 μg/l of 2, 4-dinitrobenzoic acid, and 3.6 μg/l of 2, 6-DNT. There was a highly significant linear correlation between the urinary concentrations of the two main metabolites of TNT, 2-amino-4, 6-dinitrotoluene and 4-amino-2, 6-dinitrotoluene. In 63 persons TNT or DNT or metabolite concentrations above the analytical detection limit were found in urine. These persons reported more frequently symptoms like bitter taste, burning eyes, and discoloration of the skin and hair than persons (n = 19) without detectable TNT and/or DNT exposure. Conclusion: During the disposal of military waste containing relevant TNT and DNT, exposure can occur of occupational-medical relevance. Biological monitoring is suitable for the early detection of possible adverse effects at workplaces exposed to TNT. Protective measures should be improved, together with adequate occupational-medical surveillance of persons exposed to nitroaromatic explosives. Further studies are necessary to exclude possible long term effects.